Superior Oblique Palsy: Efficacy of Isolated Inferior Oblique Recession in Cases with Ipsilateral Hypertropia in Abduction. Issue 1 (2nd January 2019) - Torrado, Laura A.; Brodsky, Michael C.
ABSTRACT: Purpose: To evaluate the effects of isolated inferior oblique (IO) muscle recession in patients with superior oblique palsy (SOP) and persistent hypertropia in abduction. Methods: Retrospective review of patients with unilateral SOP who were treated with isolated IO recession by a single surgeon (MCB) between January 2008 and December 2017. We included patients with congenital and acquired fourth nerve palsies, with a hyperdeviation of less than 20 prism diopters in primary position and at least 4 prism diopters in abduction by prism and alternate cover test (PACT) during distance fixation. A minimum follow-up of 4–6 weeks was required. Age at surgery, etiology, presence of head tilt, motor alignment in primary and secondary gaze positions at distance and near using PACT, versions, ductions, and torsion were recorded from the patients' chart. Results: Seven patients with SOP were included in this study. Four (57.14%) males, with a mean age at presentation of 41.86 years (range: 6–66 years). Mean follow-up was 13.25 months (range: 1.3–52.2 months). A decrease in mean central gaze hypertropia from 11.4 to 1.71 PD was found. A mean contralateral gaze hypertropia that decreased from 22.28 to 5.71 PD and an ipsilateral gaze hypertropia that improved from 5.86 to 1.14 PD were also noted. Torsion had a mean change of 3.4° of incyclodeviation at the final examination. Conclusions: This study confirms the efficacy of isolated maximal IO recession for the treatment of unilateral SOP that is accompanied by a modest hypertropia of the paretic eye in abduction.